Supply-driven evolution: Mutation bias and trait-fitness distributions can drive macro-evolutionary dynamics - Xue, Zhun Ping; Chindelevitch, Leonid; Guichard, Frédéric (Frontiers in Ecology and Evolution, 2023)
Many well-documented macro-evolutionary phenomena still challenge current evolutionary theory. Examples include long term evolutionary trends, major transitions in evolution, conservation of certain biological features such as hox genes, and the episodic creation of new taxa. Here we present a framework that may explain these phenomena. We do so by introducing a probabilistic relationship between trait value and reproductive fitness. This integration allows mutation bias to become a robust driver of long term evolutionary trends against environmental bias, in a way that is consistent with all current evolutionary theory. In cases where mutation bias is strong, such as when detrimental mutations are more common than beneficial mutations, a regime called "supply-driven" evolution can arise. This regime can explain the irreversible persistence of higher structural hierarchies, such as happens in the major transitions in evolution. We further generalize this result to the long-term dynamics of phenotype spaces. We show how mutations that open new phenotype spaces can become frozen in time. At the same time, the new possibilities may be observed as a burst in the creation of new taxa.